Supportive Care During Pediatric Hematopoietic Stem Cell Transplantation: Prevention of Infections. A Report From Workshops on Supportive Care of the Paediatric Diseases Working Party (PDWP) of the European Society for Blood and Marrow Transplantation (EBMT) - Ifversen, Marianne; Meisel, Roland; Sedlacek, Petr; Kalwak, Krzysztof; Sisinni, Luisa; Hutt, Daphna; Lehrnbecher, Thomas; Balduzzi, Adriana; Diesch, Tamara; Jarisch, Andrea; Güngör, Tayfun; Stein, Jerry; et al. (Frontiers in Pediatrics, 2021)
Specific protocols define eligibility, conditioning, donor selection, graft composition and prophylaxis of graft versus host disease for children and young adults undergoing haematopoietic stem cell transplant (HSCT) . However, international protocols rarely, if ever, detail supportive care, including pharmaceutical infection prophylaxis, physical protection with face masks and cohort isolation or food restrictions. Supportive care suffers from a lack of scientific evidence and implementation of practices in the transplant centers brings extensive restrictions to the child’s and family’s daily life after HSCT. Therefore, the Board of the Paediatric Diseases Working Party (PDWP) of the European Society for Blood and Marrow Transplantation (EBMT) held a series of dedicated workshops since 2017 with the aim of initiating the production of a set of minimal recommendations. The present paper describes the consensus reached within the field of infection prophylaxis including an updated vaccination program, guidelines for microbial prophylaxis and restrictions following discharge until full de-isolation